Exergame Grading Scheme: Concept Development and Preliminary Psychometric Evaluations in Cancer Survivors. (2nd October 2017) - Wang, Hsiao-Lan; Liu, Chiung-Ju; Kilpatrick, Marcus; Jim, Heather; McMillan, Susan; Vijayakumar, Nisha; McDonald, Sally; Padhya, Tapan; Russell, Jeffery; Vondruska, Karen; Visovsky, Constance
Abstract : The challenge of using exergames to promote physical activity among cancer survivors lies in the selection of the exergames that match their fitness level. There is a need for a standardized grading scheme by which to judge an exergame's capacity to address specific physical fitness attributes with different levels of physical engagement. The study aimed to develop an Exergame Grading Scheme and preliminarily evaluate its psychometric properties. Fourteen (14) items were created from the human movement and exergame literature. The content validity index (CVI) was rated by content experts with two consecutive rounds (N = 5 and N = 3 independently). The interrater reliability (IRR) was determined by two raters who used the Exergame Grading Scheme to determine the grading score of the five exergames performed by two cancer survivors (N = 10 ). Each item had a score of 1 for item-level CVI and 1 for k . For IRR, 9 items had rho values of 1, 1 item had 0.93, and 4 items had between 0.80 and 0.89. This valid and reliable Exergame Grading Scheme makes it possible to develop a personalized physical activity program using any type of exergame or fitness mobile application in rehabilitation practice to meet the needs of cancer survivors.